Does the housing provident fund cause housing inequality? The micromechanism and macroeffect in China - Anquan Zhang; Lu Liu (Financial Innovation)
Abstract This study explores the housing distribution effect of the Housing Provident Fund (HPF) system on households. Utilizing data from the China Household Finance Survey conducted in 2013, 2015, 2017, and 2019, this study empirically investigates this effect from two dimensions: the impact of HPF payments on household income and housing loan behavior, and the impact on the Gini coefficient of housing assets within the group. The results indicate that the HPF payment does not significantly impact household income levels. Instead, it increases their likelihood of obtaining housing loans, particularly for middle-income households. Additionally, for any group of families, the HPF payment decreased the housing Gini coefficient among households by approximately 0.11 units. This study may be the first to provide the most direct empirical evidence on the extent of HPF’s impact on housing inequality within a group. It also questions the inference in the literature that “HPF will aggravate housing inequality within the group.” Based on this study’s findings, we expect that housing inequality will continue to be alleviated with continued HPF implementation. In particular, this effect will be more significant if the credit support for low-income families to purchase houses through the HPF can be further enhanced.